Artisanal and small-scale gold mining: a cross-sectional assessment of occupational mercury exposure and exposure risk factors in Kadoma and Shurugwi, Zimbabwe - Mambrey, Viola; Rakete, Stefan; Tobollik, Myriam; Shoko, Dennis; Moyo, Dingani; Schutzmeier, Paul; Steckling-Muschack, Nadine; Muteti-Fana, Shamiso; Bose-O’Reilly, Stephan (Academic Press, 2021)
In artisanal and small-scale gold mining (ASGM) the toxic metal mercury is used for gold extraction. The objective of this cross-sectional study was to assess mercury concentrations in urine and blood and mercury-related symptoms of participants identifying themselves as miners from Kadoma and Shurugwi, Zimbabwe. Moreover, we aimed to explore possible risk factors influencing mercury body burden. In 2019, urine and blood samples of 207 participants were collected and analyzed for mercury using atomic absorption spectroscopy. All participants answered questions regarding their exposure risks. The median urine mercury value was 4.75 μg/L with a maximum of 612 μg/L. Median mercury concentration in creatinine corrected urine values was 3.98 μg/g with a maximum value of 478 μg/g. The median blood mercury value was 2.70 μg/L with a maximum of 167 μg/L. Correlations between exposure risks factors such as the lack of retort use and elevated mercury values were demonstrated. ASGM is very common in Zimbabwe. Thus, mercury exposure is a major occupational health risk for miners. Moreover, this study emphasizes the impact of exposure risk factors on the mercury body burden.